Discharge Planning-based Information System to Improve Compliance among Preeclampsia Patients - Tri Endah Widi Lestari; Ari Suwondo; Budiyono Budiyono (Alta Dharma Publisher, 2020)
Complications of pre-eclampsia cause the highest Maternal Mortality Rate (MMR) in the puerperium. One of the successes lies in the success of AKI prevention care in the postpartum with promotive and preventive efforts. Promotive implemented through discharge planning when hospitalization and preventive back control of maternal postpartum preeclampsia. The study aimed to analyze the discharge planning based information system to improve compliance among preeclampsia patients. The study used a quasi-experiment, pre-test, and post-test with a non-equivalent control group design. The samples allocated into an intervention group (n=17) and control group (n=17) and conducted at Bagas Waras hospital. Interventions performed for 30 minutes and frequency 3x, discharge planning, and evaluation is done on days 7 and 14 postpartum. The results showed that there is a significant difference in the level of re-control compliance between before and after the intervention group with p= 0.001 and a control group with p= 0.008. In addition, there is a significant difference in the level of re-control compliance between the intervention and control groups with p= 0.018. Whereas, there is a significant effect between models of discharge planning pre-eclampsia based on information systems of re-control compliance with p = 0.014. The discharge planning of preeclampsia based on the information systems effectively used as a tool for improving the re-control compliance of postpartum preeclampsia in the hospital